PENGARUH PEMINDAHAN SUTT 150 KV CELUKAN BAWANG – KAPAL TERHADAP ALIRAN DAYA SISTEM BALI - Fauzi, Muhammad; Sukerayasa, I W; Ariastina, W.G. (Jurnal Teknologi Elektro; Vol 17 No 1 (2018): (Januari - April) Majalah Ilmiah Teknologi Elektro, 2018)
To meet the energy needs in Bali Island which is increasing by 6 - 9% in the next 5 years, the government has been working on the development of Celukan Bawang power plant. The Celukan Bawang power plant project completed since 2013 has been fully operational in August 2015 as an outlet for the transmission of 150kV High Voltage Air Line (SUTT) transmission. Related to the issue of social issues with the keyword of Desa Celukan bawang on the development which is the home for them SUTT, the PT PLN (PERSERO) is asked to implement a strategy for securing the distribution so that the Bali system is safe when the re-route SUTT route. From the simulation result using PSSE Tools, Bali's electric power flow is simulated in 3 scenarios. Scenario 1 is free 1 Circuit Celukan Onion - Ships and Operation of the plant in accordance with the order, scenario 2 off 1 circuit Celukan Onion - Ship and acceleration Plant in South Line, and scenario 3 is done by loose both Celukan Onion - Ship and Southern remote operation. Based on the results of the analysis of the following scenarios filled scenario 1 has more economic value, reliable and quality compare other scenarios.